Health Disparities of Sexual Minority Patients Following Prostate Cancer Treatment: Results From the Restore-2 Study - Rosser, B. R. Simon; Polter, Elizabeth J.; Talley, Kristine M. C.; Wheldon, Christopher W.; Haggart, Ryan; Wright, Morgan; West, William; Mitteldorf, Darryl; Ross, Michael W.; Konety, Badrinath R.; Kohli, Nidhi (Frontiers in Oncology, 2022)
Abstract: Purpose: The NIH has identified sexual and gender minority persons as a health disparity population but little is known about cancer outcomes in these populations. The purpose of this study was to identify disparities in sexual minority prostate cancer patient-reported outcomes, to examine within group differences, and to test for alternative explanations for identified differences. Materials and Methods: In 2019, we recruited 401 gay and bisexual prostate cancer patients into the Restore-2 study, a randomized controlled trial of rehabilitation program tailored for sexual minority men. Results: Compared to the normative (heterosexual) EPIC sample, participants had significantly worse urinary, bowel and hormonal function, better sexual function, and no difference on bother scores. They also had worse depression and overall mental health, and worse physical, social/family, functional, prostate specific and overall well-being quality of life outcomes. Across measures, no differences by age, gay versus bisexual orientation, race/ethnicity, and relationship status were observed. Those who had hormonal treatment had worse sexual and hormonal function than those who had radiation or surgery only. Those with a longer time since treatment had better urinary function. Differences remained when participants were matched to normative samples on cancer stage and time since treatment. Conclusions: This, the largest study of sexual minority prostate cancer patients to date, confirms health disparities in prostate cancer quality of life outcomes. Findings appear reliable and robust. To improve the clinical care of prostate cancer, it will be important to address the health disparities experienced by sexual minority prostate cancer patients.